Understanding Law in Contextual Pluralism: A Preface. (12th May 2022) - Wang, Shucheng
Abstract: Law has become increasingly important in China's development. However, the nature and function of law in China's context can hardly be understood and explained by traditional legal concepts and theories. With a global rise of authoritarianism, the Symposium on 'Sources of Law, Authoritarian Legality and Chinese Jurisprudence' critically examines the sources of law, authoritarian legality, and Chinese jurisprudence from an interdisciplinary perspective. The discussion of the symposium covers the theoretical relationship between the Party and law and its practical implications, the dynamics of Chinese law and governance, theoretical challenges from, and reflections on, the development of intraparty regulations, and China's jurisprudence of international law, as well as the instantiation of legal instrumentalism in China's context.